2008
DOI: 10.1177/1352458508098269
|View full text |Cite
|
Sign up to set email alerts
|

The results of two multicenter, open-label studies assessing efficacy, tolerability and safety of protiramer, a high molecular weight synthetic copolymeric mixture, in patients with relapsing–remitting multiple sclerosis

Abstract: Objective Two pilot studies were conducted to evaluate safety, tolerability, and efficacy of two doses of Protiramer in patients with relapsing-remitting multiple sclerosis. Background Both glatiramer acetate and TV-5010 are synthetic copolymers comprised the same four amino acids in a defined molar ratio. TV-5010 has higher average molecular weight than Glatiramer acetate and might be hypothesized that glatiramoids with higher molecular weight might be more immunoreactive than lower molecular weight peptides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 8 publications
(8 reference statements)
0
24
0
2
Order By: Relevance
“…These adverse effects were observed in 50% of patients in the low protiramer dose (15 mg/wk) and 89% of patients in the higher dose (30 mg/wk; De Stefano et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These adverse effects were observed in 50% of patients in the low protiramer dose (15 mg/wk) and 89% of patients in the higher dose (30 mg/wk; De Stefano et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…This minor change results in a product with a different MW distribution and different biological properties than GA (De Stefano et al 2009;Varkony et al 2009). Based on encouraging preclinical safety results from short-term toxicity studies, protiramer's safety, tolerability, and efficacy were evaluated in two small phase II clinical trials in MS patients; it demonstrated good general safety and tolerability (De Stefano et al 2009). Later, long-term preclinical toxicity studies in monkeys and rats revealed marked progression in the severity of injection site reactions, which was also accompanied by kidney and liver damage, and death of some high-dose animals.…”
Section: Introductionmentioning
confidence: 99%
“…As the branded patent is set to expire, competition with biosimilars may emerge. Glatiramoid compounds are under study and may add to the competition [103]. The field of effective treatments for RRMS continues to grow.…”
Section: Clinical Usementioning
confidence: 99%
“…Copaxone ® is a random copolymer based on four amino acids (L-alanine, L-lysine, L-glutamic acid and L-tyrosine) with Mw within the range of 5000-10000 Da for the treatment of multiple sclerosis [113,114]. After subcutaneous administration, it reduces frequency of relapse and disease progression [115]. In the early 90s, Poly(Arg-Gly-Asp) was demonstrated to inhibit lung metastasis and migration of B16-BL6 melanoma in mice [116,117].…”
Section: Drug Deliverymentioning
confidence: 99%